Valorization of spent coffee grounds for scented candle production - Abd Rahman, N. A.; Azhar, N. A.R.M.; Taip, F. S. (Rynnye Lyan Resources, 2025)
Approximately 6 million t of spent coffee grounds (SCG) are produced annually but only 25% are reused and the rest ends up in landfills. One of the potentials of SCG is its use as a scented candle. This is due to low moisture and ash content, and high oil fraction of SCG. This research aimed to investigate the physicochemical properties of different types of SCG and the suitability of the SCG to be used in scented candle making. SCG from different brewing methods such as moka pot and espresso were used in this study. The physicochemical properties of these SCGs were analysed. In candle making, different concentrations of SCG were applied, ranging from 20 to 50%. From the results, it could be seen that the physicochemical properties of the moka pot and espresso-brewed SCG were different, which could affect the performance of the scented candle produced using the SCG. The burning performance such as wax consumption rate, pool size, and flame height, were measured. In conclusion, the suitable concentration of SCG in scented candle making was found to be 30% and 40% for the Moka pot with the addition of soy wax, 20% for espresso concentration, and 30% for the Moka pot with the addition of paraffin wax.